Reducing urban poverty in the global South - Satterthwaite, David (Routledge, 2014)
This isthe first book to review the effectiveness of different approaches to reducing urban poverty in the Global South. It describes and discusses the different ways in which national and local governments, international agencies and civil society organizations are seeking to reduce urban poverty. Different approaches are explored, for instance; market approaches, welfare, rights-based approaches and technical/professional support. The book also considers the roles of clientelism and of social movements. Case studies illustrate different approaches and explore their effectiveness. Reducing Urban Poverty in the Global South also analyses the poverty reduction strategies developed by organized low-income groups especially those living in informal settlements. It explains how they and the federations or networks they have formed have demonstrated new approaches that have challenged adverse political relations and negotiated more effective support. Local and national governments and international agencies can become far more effective at addressing urban poverty at scale by, as is proposed in this book, working with and supporting the urban poor and their organizations.